Satélites estabilizados por rotação e torque de radiação solar direta - Borderes Motta, Gabriel [UNESP] (2011)
The aims of this work are to analyze the direct solar radiation pressure torque (TPRS) in the rotational motion of spin-stabilized artificial satellites, to numerically implement these solutions and to compare the results with real data of the Brazilian Satellite Data Collection – SCD1 and SCD2, supplied by INPE. The mathematical model for this torque is determined for a cylindrical satellite, and the components of this torque are determined in a fixed system in the satellite. An analytical solution for the spin motion equations is proposed, in which TPRSD does not affect the spin velocity of the satellite. Two approaches are adopted in the numerical implementation of the developed theory: the first one considers the proposed theory and the second introduces a variation in the spin velocity based on its real variation. The results obtained indicate that the solar radiation pressure torque has little influence in the right ascension and declination axis of rotation due to the small dimension of the satellite and altitude in which it is found. To better validate the application of the presented theory, the angular deviation of the spin axis and solar aspect angle were also analyzed. The comparison of the results of the approaches conducted with real data show good precision in the theory, which can be applied in the prediction of the rotational motion of the spin-stabilized artificial satellites, when others external torques are considered besides the direct solar radiation pressure torque